P422 EARLY EXERCISE PRESCRIPTION AFTER ACUTE CORONARY SINDROME. A NEW MODEL FROM BEDSIDE TO THE COMMUNITY. (18th May 2022) - Lordi, R; Veronese, S; Mandini, S; Raisi, A; Piccinini, A; Ferro, A; Zerbini, V; Piva, T; Grazzi, G; Biagio, S; Pasanisi, G
Abstract: Purpose: Physical inactivity is a major risk factor and negative prognostic index of cardiovascular disease. It is necessary to define effective strategies to direct patients after an acute coronary syndrome (ACS) to physically active lifestyle. The aim of this study was to examin efficacy, feasibility and long term adherence of a new physical activity prescription, adapted to patients (pts) early after ACS. Methods: 34 pts, mean age 67years, hospitalized for ACS, were enrolled consecutively and randomized 2:1 in treatment (TR) group (n = 23) or in control (CT) group. All pts were evaluated before discharge from hospital (T0) through Quality of Life (QoL) SF12 questionnaire, determination of physical activity during free time, six–minute walking test (6MWT). All pts were orally advised about the importance of changing life–style as recommended by current international guidelines. At T0, pts in the TR group performed a 500m moderate and perceptually–regulated (11–13 on the 6–20 Borg scale) treadmill walking test (500–m TWT) to estimate peak oxygen uptake (VO2peak). A home–based physical activity based on walking, was provided to pts in the TR group: it was recommended to maintain the level of perceived intensity of effort as indicated during 500m–TWT. These pts also received a reinforce phone–call at 2 and 4 weeks (T1 and T2), that allowed monitoring the adherence to the programme. All pts were finally evaluated 8 weeks after enrollment (T3) through the same tests performed at T0. Results: Pts of the TR group at T3 reported significative improvement, compared to T0, in 6MWT (+79 m, p < 0.001), QoL (expressed in the items of SF12), usual physical activity during free time (+13MET/h/week, p < 0.001), VO2peak (+4 mL/kg/min, p < 0.001). Compliance to the programme resulted optimal since all TR group pts continued the planned physical activity for all the follow–up. Conclusions: Results of this study on efficacy, feasibility and compliance of a new model of secondary prevention programme, suggest the importance of implementing programmes of tailored physical activity schedules, based on walking, that can be safetly started soon after clinical stabilization of ACS.